Generalization of Caputo-Fabrizio Fractional Derivative and Applications to Electrical Circuits - Alshabanat, Amal; Jleli, Mohamed; Kumar, Sunil; Samet, Bessem (Frontiers in Physics, 2020)
A new fractional derivative with a non-singular kernel involving exponential and trigonometric functions is proposed in this paper. The suggested fractional operator includes as a special case Caputo-Fabrizio fractional derivative. Theoretical and numerical studies of fractional differential equations involving this new concept are presented. Next, some applications to RC-electrical circuits are provided.